A Cultural Heritage Management Perspective: Kotabaru, Yogyakarta, between a Protected Cultural Site and a Commercial Area - Fahmi Prihantoro (Humaniora, 2021)
Yogyakarta’s Kotabaru area is one of rich cultural heritage, with a protected cultural status that means it must be preserved. Presently, Kotabaru faces the threat of destruction as a consequence of its developing business and services sectors. The changing of building functions, together with new developments, is ever-increasing with each year. This research sought to study what is occurring between the preservation of the Kotabaru area and the development of its economic sector, as well as how efforts can be made to solve the problems of the threat of destruction to protected cultural sites within the area, using the Historic Urban Landscape (HUL) approach. The findings revealed that there are competing interests in the Kotabaru area, between preservation and economic development, which contribute to the emergence of a threat to the preservation of protected cultural sites. To solve this problem, the HUL approach should be used and, in particular, the approach contained in the UNESCO recommendation on managing cultural heritage. With these findings, it is hoped that they will be able to serve as a reference concept for the solving of the issues that are occurring in the Kotabaru area, from a perspective of cultural heritage management.